The Family Language Policy of Javanese Multilingual Families - Fitriati, Anna (Universitas Sanata Dharma, 2023)
Javanese is one of the regional languages with a relatively large number of speakers, around 68 million. This significant number of speakers is essential for the Javanese language to survive. Even so, the popularity of the Javanese language tends to decrease, especially among young people. This decline is influenced by various factors. One of them is that young families no longer introduce Javanese as the primary means of communication within the family. This study is interested in identifying the language attitudes of parents in Javanese families who are bilingual towards Indonesian, English, and Javanese. Furthermore, this study aims to analyze how the language policy is implemented in the family. This study combines quantitative and qualitative approaches using data collection techniques through questionnaires, interviews, and participatory observation. Data analysis shows that parents have positive language attitudes towards Indonesian and English. However, their language attitude towards Javanese is not as positive as Indonesian and English. This language attitude is reflected in the implementation of language policies in families where parents prefer to apply mixed language policies.